Morphological and Biochemical responses of Cof fee Seedlings (Cof fea arabica L.) to Foliar Application of ZnO and ZnO/Ag Nanoparticles - Pérez-Madrigal, Vicente; Rodriguez-Larramendi, Luis Alfredo; Santiago-Salazar, Didier; Orantes-Calleja, Paula Deyanira; Salas-Marina, Miguel Ángel; Pola-Albores, José Francisco; Cruz-Macías, Wel Olvein (REVISTA TERRA LATINOAMERICANA, 2025)
The application of nanotechnologies in agriculture has gained in importance in recent years, and their impact on plant growth and development has been documented with successes and limitations. In the case of cof fee cultivation, it is a viable alternative compatible with mineral fertilization schemes. The objective of this research was to study the physiological ef fect of zinc oxide nanoparticles (ZnONPs) and silver-impregnated zinc oxide (ZnONPs/AgNPs), synthesized through the sol-gel method on vegetative growth, total chlorophyll concentration, and the synthesis of functional groups in cof fee (Cof fea arabica L.) seedlings. The nanoparticles were characterized by X-ray dif fraction (XRD) and applied to the leaves. Plant height, stem diameter, leaves per plant, and leaf area, concentration of total chlorophylls and functional groups were measured by FT-IR spectroscopy. X-ray dif fraction (XRD) analysis confirmed the crystalline nature of the synthesized nanoparticles, which showed sharp peaks consistent with the hexagonal wurtzite structure, while the ZnONPs/AgNPs showed structures corresponding to the cubic phase of metallic silver. A 58.18% increase in plant height was observed upon application of ZnONPs compared to the control, and 34.78% increase in the number of leaves per plant. The highest chlorophyll concentration was recorded when combining ZnONPs+2.5AgNPs plus fertilizer, with an increase of 81.8% with respect to the control. The combined treatment of ZnONPs/AgNPs with fertilizer significantly increased the accumulation of compounds such as caf feine, sucrose, and carbohydrates. These results demonstrate the potential of nanofertilizers as growth promoters and modulators of functional metabolism in cof fee seedlings, although direct parameters of productivity and bean quality were not evaluated.